1995
DOI: 10.1021/cm00059a002
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis and Characterization of Two- and Three-Dimensional Solids of the Oxovanadium(IV)-Phosphite System. The Structures of [HN(Me)(CH2CH2)2N(Me)H]- [(VO)4(OH)2(HPO3)4], [H2N(CH2CH2)2NH2][(VO)3(HPO3)4(H2O)2], and [VO(HPO3)(H2O)]

Abstract: Hydrothermal Synthesis and Characterization of Two-and Three-Dimensional Solids of the Oxovanadium(IV)-Phosphite System. The Structures of [HN(Me)(CH2CH2)2N(Me)H]-[(V0)4(0H)2(HP03)4], [H2N(CH2CH2)2NH2][(V0)3(HP03)4(H20)2], and [V0(HP03)(H20)]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(36 citation statements)
references
References 0 publications
2
34
0
Order By: Relevance
“…The P atom adopts psuedo-pyramidal coordination geometry, which is coordinated to three O atoms with bond lengths of 1.515(4) Å for P-O1, 1.509(4) Å for P-O4 and 1.515(4) Å for P-O5, respectively, thus there are no terminal, ''pendant'' P-O or P-OH bonds [9], and a P-H bond makes up the fourth vertex of each [HPO 3 ] 2À tetrahedron. The terminal P-H bond length is 1.34(4) Å which is similar to the P-H bond length reported in H 3 PO 3 previously [3]. The existence of P-H bond is also verified by IR spectrum, which exhibits strong absorption at 2397 cm À1 [4].…”
supporting
confidence: 85%
See 2 more Smart Citations
“…The P atom adopts psuedo-pyramidal coordination geometry, which is coordinated to three O atoms with bond lengths of 1.515(4) Å for P-O1, 1.509(4) Å for P-O4 and 1.515(4) Å for P-O5, respectively, thus there are no terminal, ''pendant'' P-O or P-OH bonds [9], and a P-H bond makes up the fourth vertex of each [HPO 3 ] 2À tetrahedron. The terminal P-H bond length is 1.34(4) Å which is similar to the P-H bond length reported in H 3 PO 3 previously [3]. The existence of P-H bond is also verified by IR spectrum, which exhibits strong absorption at 2397 cm À1 [4].…”
supporting
confidence: 85%
“…It is well known that the pyramidal hydrogen phosphite group ½HPO 2À 3 , different from phosphate ½PO 3À 4 , only link three adjacent cations via P-O-M (M = metal) bonds, so it provides variety and novelty to the structures. Since the vanadium phosphites with piperazinium cations as structurally directing agents [H 2 NC 4 H 8 NH 2 ][(VO) 3 (HPO 3 ) 4 (H 2 O) 2 ] were synthesized by Zubieta and co-workers [3], a number of studies on the metal phosphites containing Zn, Co, Fe, V, Mn and Cr have been carried out [4] [6] have been reported. Some of microporous indium phosphates containing organically templates have been prepared [7], but the indium phosphites are under developed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…has attracted considerable attention [10][11][12][13]. Harrison et al [14] reported the first organically templated zincophosphite.…”
Section: Introductionmentioning
confidence: 99%
“…Following the initial reports on several novel transition metal phosphites (e.g., the organically templated vanadium phosphites [2]), manganese phosphites [3,4], cobalt phosphite [5], and zinc phosphites [6][7][8] the replacement of phosphate with phosphite in the transition metal phosphates has attracted more and more research efforts. Our group has developed the hydrothermal synthesis of many novel metal phosphites [9][10][11].…”
mentioning
confidence: 99%